2012
DOI: 10.1021/ie201635w
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of Tannery Wastes under Fast and Slow Pyrolysis Conditions

Abstract: The pyrolysis of a chromium-tanned waste (bovine split leather) under inert atmosphere has been carried out in a vertical lab scale reactor. The influence of process conditions, such as temperature, residence time, and heating rate on the pyrolytic product distribution has been studied, in order to optimize the liquid fraction obtained. Flash pyrolysis at three different temperatures (450, 500, and 550°C) and slow pyrolysis up to 750°C have been performed. Results indicate that, in the range of low temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
4
24
0
Order By: Relevance
“…Marcilla et al studied the analytical pyrolysis of tanned-leather using a Pyroprobe device, to compare the effects of different organic and inorganic tanning agents [14,15]. Marcilla et al also evaluated the pyrolysis of chromium-tanned wastes and a commercial collagen to study the effect of the tanning process [16].…”
Section: Introductionmentioning
confidence: 99%
“…Marcilla et al studied the analytical pyrolysis of tanned-leather using a Pyroprobe device, to compare the effects of different organic and inorganic tanning agents [14,15]. Marcilla et al also evaluated the pyrolysis of chromium-tanned wastes and a commercial collagen to study the effect of the tanning process [16].…”
Section: Introductionmentioning
confidence: 99%
“…Sludge, a by-product of wastewater treatment, which contains a large number of pathogens, heavy metals, and organic matter, is defined as waste (Marcilla et al, 2012). Until now, several disposal methods of sludge including incineration (Kavouras et al, 2015), anaerobic digestion (Zupancic and Jemec, 2010), landfilling (Celary and Sobik-Szoltysek 2014), and application in agriculture or building materials (Swarnalatha et al, 2006) have been reported, and each has its own advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis technology, as the best available thermochemical conversion technology, has attracted great attention since it can turn waste into gas, liquid, and solid residue (Marcilla et al, 2012;Thangalazhy-Gopakumar et al 2015). The pyrolytic gas and liquid can be applied in fuel or chemical feedstock after improvement, and the solid residue, char, was used as cheap adsorbents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations